2020
DOI: 10.1027/1016-9040/a000380
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Memory Development Across the Lifespan

Abstract: Abstract. Prospective Memory (PM; i.e., the ability to remember to perform planned tasks) represents a key proxy of healthy aging, as it relates to older adults’ everyday functioning, autonomy, and personal well-being. The current review illustrates how PM performance develops across the lifespan and how multiple cognitive and non-cognitive factors influence this trajectory. Further, a new, integrative framework is presented, detailing how those processes interplay in retrieving and executing delayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 67 publications
(101 reference statements)
7
36
0
Order By: Relevance
“…For instance, in attention-demanding PM tasks, age-related decreases can be generally expected. Moreover, it is well documented that older adults perform less well than younger adults in event-based PM in the laboratory (e.g., Ballhausen, Schnitzspahn, Horn, & Kliegel, 2017;Horn et al, 2013;Schnitzspahn et al, 2012;Zuber & Kliegel, 2020). Specifically, for event-based PM tasks involving so-called nonfocal target events (in which the target features are not necessarily relevant for the ongoing-task decisions) theories of PM have assumed that engagement of attention-demanding processes is necessary, directed toward identifying targets (e.g., Horn & Bayen, 2015;McDaniel & Einstein, 2007;Scullin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in attention-demanding PM tasks, age-related decreases can be generally expected. Moreover, it is well documented that older adults perform less well than younger adults in event-based PM in the laboratory (e.g., Ballhausen, Schnitzspahn, Horn, & Kliegel, 2017;Horn et al, 2013;Schnitzspahn et al, 2012;Zuber & Kliegel, 2020). Specifically, for event-based PM tasks involving so-called nonfocal target events (in which the target features are not necessarily relevant for the ongoing-task decisions) theories of PM have assumed that engagement of attention-demanding processes is necessary, directed toward identifying targets (e.g., Horn & Bayen, 2015;McDaniel & Einstein, 2007;Scullin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, records in other languages, commentaries, narrative/qualitative reviews, editorials, book chapters, and abstracts were not considered for further analysis. The following exclusion criteria were also applied: (a) studies that manipulated the cognitive load of the PM cue (e.g., Ballhausen et al, 2017 ; Cohen, 2013 ), as these conditions have been shown to affect OT performance ( Meier & Zimmermann, 2015 ), (b) studies that included delay-execute conditions or activity-based PM tasks (i.e., the PM response had to be performed after a particular task has finished; Brewer et al, 2011 ), as PM cues did not appear during the OT, (c) studies that included clinical samples, as PM might be particularly affected in this context (e.g., Albinski et al, 2012 ), (d) studies that involved drug interventions and/or ingestion of substances (e.g., Rusted, & Trawley, 2006 ), or that manipulated other factors including sleep (e.g., Barner et al, 2016 ), or that used neuromodulation techniques such as transcranial magnetic stimulation (e.g., Basso et al, 2010 ), (e) experiments that included children, adolescents, and older adults (e.g., Cheie et al, 2017 ; Zollig et al, 2007 ) given that previous research had demonstrated that PM follows an inverted U-shape developmental trajectory ( Zuber & Kliegel, 2019 ; Zimmermann & Meier, 2006 ). So, by including only young and middle-age adults, age effects were somewhat restricted to this developmental stage.…”
Section: Methodsmentioning
confidence: 99%
“…(ii) To examine the effects of age (from 9 to 13 years), gender, and their possible interaction on the EPELI measures. As executive functions (Best & Miller, 2010;Klenberg, 2015) and prospective memory (Ballhausen et al, 2019;Mahy et al, 2014;Zuber et al, 2019;Zuber & Kliegel, 2020) continue developing during the early school years and beyond, we expected to see better EPELI performances (higher total scores and efficacies) in older children within our age range. Even though the issue of gender differences in executive functions is controversial, there is some evidence that males may be more impulsive than females across the lifespan (for a review, see Grissom & Reynes, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…To this end, children also performed an instruction recall task, in which they orally repeated a list of tasks similar to those that they executed in EPELI. Studying the associations between the instruction recall task and EPELI was expected to clarify the links between encoding and execution, which are intertwined in prospective memory performance (Kliegel et al, 2008; see also Zuber & Kliegel, 2020).…”
Section: (Iii)mentioning
confidence: 99%